Pengaturan Pembentukan Daerah Khusus dan Daerah Istimewa di Indonesia - Satria Hanas, Clinton; Y. Stefanus, Kotan; G. Tuba Helan, Yohanes (Journal of Comprehensive Science, 2024)
The lack of clarity regarding the determination of an autonomous region to become a special region and a special region even though the 1945 Constitution of the Republic of Indonesia has been regulated in Article 18. But regarding how the mechanism and conditions that can be met by a region to be a special region and a special region do not have definite rules. This research is a normative legal research with statutory, conceptual, historical and comparative approaches that apply to determine the overall legal regulations. The results show that the regulation of the status of regions (symmetrical decentralization), special regions and special regions in Indonesia is regulated in Article 18 of the 1945 Constitution; The Local Government Act is a derivative arrangement of Article 18 although it regulates thoroughly about how the requirements for the formation of regions (symmetrical decentralization) but does not regulate the requirements for the formation of special regions and special regions in the Act such as regions (symmetrical decentralization), there is only recognition of special regions and special regions; So it is necessary for future laws to accommodate this.